Determinants of Environmentally Sustainable Food Security: A Factor-Based Review for Indonesia's Sustainability - Silvia Rahayu; Dewi Ernita; Suci Marselina (The Future of Education Journal, 2026)
This study aims to examine the effects of per capita income, food imports, carbon emissions, and fertilizer use on food security in Indonesia during the 2010–2023 period. Annual data were obtained from various official sources and analyzed using the Two-Stage Least Squares (2SLS) method to address potential endogeneity issues among the independent variables. The results indicate that, simultaneously, all four variables have a significant effect on food security, with an R-squared value of 92.68% and a Durbin–Watson statistic of 1.954, suggesting that the model is free from autocorrelation. Partially, carbon emissions have a positive and statistically significant effect, with a coefficient of 173.974 (p = 0.0010), indicating that the intensity of economic activity contributes substantially to improving food security. In contrast, fertilizer use has a negative and statistically significant effect, with a coefficient of −44.154 (p = 0.0261), suggesting that inappropriate fertilizer policies may reduce food security due to land degradation. Meanwhile, per capita income and food imports exhibit positive but statistically insignificant effects on food security. Based on these findings, the study recommends reforming fertilizer policies based on site-specific land requirements, promoting sustainable and low-emission agricultural practices, strengthening food logistics infrastructure, and reducing dependence on food imports. Future studies are encouraged to extend the observation period, incorporate additional variables such as climate change and agricultural land area, and employ spatial or regional panel data approaches to provide more comprehensive findings.